Students' Understanding of Climate Change after Learning using Immersive Virtual Learning - Mufida, Asita Al; Widodo, Ari; Solihat, Rini (Jurnal Pendidikan MIPA, 2022)
Immersive Virtual Learning is a learning that is considered meaningful for students to learn the complex concept of climate change because of the many interactions of the systems involved in it, and is considered a concept that is quite challenging for students. It is known that there are still many students who have limited knowledge about climate change so that learning methods are needed that can help them understand the concept of climate change well. This study aims to see how students' understanding after learning using the Immersive Virtual Learning method, and compared with conventional learning methods. Using the Pre-Post Experiment Control Group Design involving 59 students who were divided into treatment and control classes, resulted in data showing that students' understanding in the two classes experienced a significant difference, but very small improvement, even though the treatment class experienced a better improvement. than the control class. Based on this, it can be concluded that students' understanding has increased slightly after learning to use the Immersive Virtual Learning method. Keywords: immersive virtual learning, understanding, climate change. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp642-650